2013
DOI: 10.4236/jmmce.2013.15035
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gas Metal Arc Welding Techniques on the Mechanical Properties of Duplex Stainless Steel

Abstract: The study has compared the effect of gas metal arc welding techniques on some mechanical properties of duplex stainless steel. The samples after welded were given post weld heat treatment (quenching in engine and neem oil). After the analyses, it was established that duplex stainless steel can be weld successfully using gas metal arc welding process (GMAW). Both Lubricating oil and neem oil can serve as quenching medium for post welding heat treatment of duplex stainless steel. The results of the studies also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…The post weld heat treatment of welded samples was carried out (quenching in engine and neem oil) and the result indicated that the post heat treatment process influenced the mechanical property of clad part made by GMAW a lot. The research also showed that the stress relief heat treatment gave better strength up to (331 MN/m 2 ) than that were quenched in lubricating oil (329 MN/m 2 ) and neem oil (222 MN/m 2 ), but the reverse trend was noticed in terms of toughness (Ibrahim et al, 2013).…”
Section: Influences Of Different Parameters On Gmaw Claddingmentioning
confidence: 85%
“…The post weld heat treatment of welded samples was carried out (quenching in engine and neem oil) and the result indicated that the post heat treatment process influenced the mechanical property of clad part made by GMAW a lot. The research also showed that the stress relief heat treatment gave better strength up to (331 MN/m 2 ) than that were quenched in lubricating oil (329 MN/m 2 ) and neem oil (222 MN/m 2 ), but the reverse trend was noticed in terms of toughness (Ibrahim et al, 2013).…”
Section: Influences Of Different Parameters On Gmaw Claddingmentioning
confidence: 85%
“…c according to BS 18 standard. Proportional sample is given by the relationship: Lo=5.56A.5emsince.5emA=πd2true/4.5emthen,.5emA=dπtrue/2=0.88d..5emThus,.5emLo=5.65*0.885d. …”
Section: Experimental Studiesmentioning
confidence: 99%
“…Duplex stainless steels are mostly selected because of their combination of high strength and corrosion resistance. Their full potential is used in locations where the material comes into contact with salt water, or where high concentrations of chlorides are present in the ambient air or where de-icing salts are of a concern [Ibrahim et al, 2013].…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%